ANALISIS GENDER PERAN WANITA SEBAGAI STIMULATOR EKONOMI KELUARGA NELAYAN DI PESISIR KABUPATEN SIDOARJO - Titis Istiqomah (Fish Scientiae, 2018)
Coastal women play an important role in supporting the creation of value-added fishery products that become the main work of her husband (Istiqomah, 2015). The role of women in the coastal district of Sidoarjo as the wife of fishermen, the wife of the fish pond owner, and the wife of the fish processor; Proven to be able to move the economy on the coast by processing and adding value to the fishery resources.The purpose of this study is to find out how big the contribution of women to create economic empowerment in coastal district of Sidoarjo from catch fishery sector, aquaculture fishery and processed. The research was conducted in the village of Banjar Kemuning Sedati sub-district, which is the center of catch fishery, in Sawohan village, Buduran sub-district as a center of aquaculture, and Penatar Sewu village, Tanggulangin sub-district as a processed fishery center; During the year 2016 -2017.The research method is terrestris survey by using questionnaire tool. Data were obtained from closed interviews on selected respondents intentionally (purposive sampling) based on information from local fisheries figures. Survey results are analyzed by using shift share method compiled with Ishikawa Effect based on Balanced Score Cards.The results show that women are able to increase income and economic empowerment of their families. The contribution of women to the increase in family income is very fantastic ranging from 42% to 115% compared to if women in the family do not make productive business. The economic participation of women has proven to be able to improve the educational achievement of their children better and wider thinking. Husbands who work well together in terms of productive business with his wife can open jobs for others, and have a wide opportunity to develop other productive businesses for husbands during the season there is no fish.